2013
DOI: 10.1371/journal.pone.0067749
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study Simultaneously Exploring the Carriage of APEC Virulence Associated Genes and the Molecular Epidemiology of Faecal and Systemic E. coli in Commercial Broiler Chickens

Abstract: Colibacillosis is an economically important syndromic disease of poultry caused by extra-intestinal avian pathogenic Escherichia coli (APEC) but the pathotype remains poorly defined. Combinations of virulence-associated genes (VAGs) have aided APEC identification. The intestinal microbiota is a potential APEC reservoir. Broiler chickens are selectively bred for fast, uniform growth. Here we simultaneously investigate intestinal E. coli VAG carriage in apparently healthy birds and characterise systemic E. coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
64
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 56 publications
11
64
2
Order By: Relevance
“…Intestinal pathogenic E. coli (IPEC) are causing diarrhoea syndromes and seldom colonize healthy humans whereas extraintestinal pathogenic E. coli (ExPEC) often innocuously colonize the gut but have the ability to cause severe infections such as meningitis or blood stream infections (Vila et al ., 2016). Recent studies compared the occurrence of certain virulence‐associated genes (VAGs) in avian pathogenic E. coli (APEC), uropathogenic E. coli (UPEC) and commensal E. coli from humans and broiler chickens (Kemmett et al ., 2013; de Carli et al ., 2015; van Hoek et al ., 2016; Paixao et al ., 2016; Silveira et al ., 2016). It turned out that certain VAGs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal pathogenic E. coli (IPEC) are causing diarrhoea syndromes and seldom colonize healthy humans whereas extraintestinal pathogenic E. coli (ExPEC) often innocuously colonize the gut but have the ability to cause severe infections such as meningitis or blood stream infections (Vila et al ., 2016). Recent studies compared the occurrence of certain virulence‐associated genes (VAGs) in avian pathogenic E. coli (APEC), uropathogenic E. coli (UPEC) and commensal E. coli from humans and broiler chickens (Kemmett et al ., 2013; de Carli et al ., 2015; van Hoek et al ., 2016; Paixao et al ., 2016; Silveira et al ., 2016). It turned out that certain VAGs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Kemmet et al (2013) reported a wide diversity and higher prevalence of APEC-associated VGs in faecal E. coli from one-day-old chicks compared to older chickens. There was a noticeable decrease in the number of APEC-associated VGs in faecal E. coli detected at slaughter (Kemmett et al, 2013). However, these variations in the prevalence among young chickens could be as a result of young birds having more diverse microbiota and negative selection in the gut for virulent strains.…”
Section: The Prevalence Of Apec Related Vgsmentioning
confidence: 96%
“…A number of overseas studies identified vectors humans (farm worker and visitors), wild birds and rodents, source and type of treatment(s) applied to the drinking water and unfavourable housing conditions as major risk factors associated with avian colibacillosis (Kemmett et al, 2013;Nolan et al, 2013;Vandekerchove et al, 2004a). Low levels of APEC on overseas poultry farms, is associated with strict farm biosecurity and management practices, such as control of vectors by minimising bird interaction with other animals and hygienic cleaning protocols Vandekerchove et al, 2004a;Zanella et al, 2000).…”
Section: Chapter 1: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations